A Regional Analysis of U.S. Insurance Reimbursement Guidelines for Massage Therapy - Miccio, MS, LMT, CEIM, Robin S.; Cowen, PhD, LMT, Virginia S. (International Journal of Therapeutic Massage & Bodywork, 2018)
Introduction: Massage techniques fall within the scope of many different health care providers. Physical therapists, occupational therapists, and chiropractors receive insurance reimbursement for health care services, including massage. Although many patients pay out of pocket for massage services, it is unclear how the insurance company reimbursement policies factor provider qualifications into coverage. This project examined regional insurance reimbursement guidelines for massage therapy in relation to the role of the provider of massage services. Methods: A qualitative content analysis was used to explore guidelines for 26 health insurance policies across seven US companies providing coverage in the northeastern United States. Publicly available information relevant to massage was obtained from insurance company websites and extracted into a dataset for thematic analysis. Data obtained included practice guidelines, techniques, and provider requirements. Information from the dataset was coded and analyzed using descriptive statistics. Results: Of the policies reviewed, 23% explicitly stated massage treatments were limited to 15-minute increments, 19% covered massage as one part of a comprehensive rehabilitation plan, and 27% required physician prescription. Massage techniques mentioned as qualifying for reimbursement included: Swedish, manual lymphatic drainage, mobilization/manipulation, myofascial release, and traction. Chiropractors, physical therapists, and occupational therapists could directly bill for massage. Massage therapists were specifically excluded as covered providers for seven (27%) policies. Conclusion: Although research supports massage for the treatment of a variety of conditions, the provider type has not been separately addressed. The reviewed policies that served the Northeastern states explicitly stated massage therapists could not bill insurance companies directly. The same insurance companies examined reimbursement for massage therapists in their western U.S. state policies. Other health care providers were able to bill directly for massage services to companies that did not accept direct billing by massage therapists. The specific exclusion of massage therapists as eligible providers violates the Affordable Care Act’s non-discriminatory provision. Massage therapists should continue to advocate for reimbursement privileges to spur wider acceptance of massage therapy in health care.